Comparison of Resistive Index, Pulsatility Index, and Arterial Waveform at the Comparison of Resistive Index, Pulsatility Index, and Arterial Waveform at the Site of Hepatic Artery Bifurcation in Patients with and without Nonalcoholic, Non-Diabetic Fatty Liver - Hussein Soleimantabar; Saeed Nasiri; Farshad Gharebakhshi; Samaneh Ahmadi (Novelty in Biomedicine)
Background: Nonalcoholic fatty liver disease (NAFLD) is common. Noninvasive methods to assess fibrosis stage are limited, and biopsy remains the gold standard. We aimed to compare the Doppler ultrasound indices (resistive index (RI), pulsatility index (PI), and arterial waveform) at the place of division of the hepatic artery in patients with and without nonalcoholic non-diabetic fatty liver.